2019
DOI: 10.2341/18-034-c
|View full text |Cite
|
Sign up to set email alerts
|

Caries Diagnosis in Dental Practices: Results From Dentists in a Brazilian Community

Abstract: The aim of this study was to assess practices related to diagnosis of dental caries among dentists (n=217) from Araraquara, São Paulo State, Brazil. Data on sociodemographic information and practitioner characteristics were collected using a pretested questionnaire, and data on practices related to caries diagnosis were gathered by using a translated and culturally adapted questionnaire from the US National Dental Practice-Based Research Network. Descriptive statistics and regression analyses were used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
12
0
5
Order By: Relevance
“…Variable levels in the knowledge of advanced dental caries diagnosis methods among dental students as well as dental practitioners were noted. This is consistent with studies from across the world that have shown that the practice of dentistry has not kept pace with the rapid advances made in the principles of dental caries diagnosis [ 37 , 38 ]. Correspondingly, in a study conducted in 2011, it was found that low use of FOTI among dentists in out-patient clinics was observed [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Variable levels in the knowledge of advanced dental caries diagnosis methods among dental students as well as dental practitioners were noted. This is consistent with studies from across the world that have shown that the practice of dentistry has not kept pace with the rapid advances made in the principles of dental caries diagnosis [ 37 , 38 ]. Correspondingly, in a study conducted in 2011, it was found that low use of FOTI among dentists in out-patient clinics was observed [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Limitations of this study include: a) the crosssectional nature of the study design; b) the use of a convenience sample from a Brazilian city that may not reflect practices on risk assessment throughout the country; c) the presumption that the reported preventive measures are actually what the dentists perform in routine practice; 19 d) the lack of questions about the use of electronic charts that may incorporate caries risk assessment systems; e) although certain socioeconomic variables were included in the study, other factors such as educational level were not. Nonetheless, the similarity of demographic characteristics among participant dentists and non-participating dentists, 38 dentists from Araraquara 14 and Brazilian 13 dentists, as well as the feasibility of the questionnaire to compare dental practice patterns globally 38 are the strengths of the study, and can help advance the knowledge base for a specific country, for an assessment of the topic on undergraduate courses, and to increase awareness among dentists seeking continuing education on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire design of the study works under the assumption that what dentists accurately reported their practice patterns doing in practice is actually what they perform routinely in their dental practices; c) dentists were asked about their overall preventive measures, not whether they gave individual patients recommendations for single or multiple treatments [25]; and d) the questions measured self-reported preventive procedures that may be influenced by social desirability and recall bias [15]. Nonetheless, the study proved to be a feasible tool to study dental practice patterns and it can be used to compare the results to other dentist populations [11].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the recruitment process and strategies to increase the response rate (pre-paid return envelope, questionnaires sent to work address; a second copy of the questionnaire to non-respondents; precontact by telephone; collection of completed questionnaires at work address) for the major study is described in a previous paper [11].…”
Section: Data Collectionmentioning
confidence: 99%